Transformational or Servant Leadership? Sebuah Studi Literatur Gaya Kepemimpinan Paling Efektif untuk Generasi Milenial dan Z - Grace Maria Fitricia; Yadi Fakhruzein Terang Jaya (International Forum of Researchers and Lecturers, 2025)
The old model of leadership style has shifted to a new model that is currently relevant to be effectively applied to lead the generation that dominates the world of work today and is entering the most productive age, namely the millennial generation and generation Z. With the young generation in Indonesia growing so rapidly with characteristics, needs and expectations that are different from the previous generation, the leadership style applied must also adjust to the rhythm and pattern of the current young generation. This research is a type of qualitative research with a literature study method or literature review. The literature study approach used in this study: the first stage is to collect literature, make comparisons from various literature sources, conduct analysis and present interpretations of the results of the analysis. From this study, it was concluded that considerations and implementations in practicing a combination of transformational leadership styles and servant leadership can be the most effective leadership style adjusted to the analysis of needs, characteristics, expectations and results of leadership practices for the millennial and Z generations in an organizational environment.